2020
DOI: 10.1016/j.geb.2020.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Social and strategic ambiguity versus betrayal aversion

Abstract: This paper examines the difference between strategic ambiguity as in game theory and ambiguity arising in individual decisions. We identify a new, non-strategic component underlying all strategic ambiguities, called social ambiguity. We recommend controlling for it to better identify strategic causes. Thus, we shed new light on Bohnet and Zeckhauser's betrayal aversion in the trust game. We first show theoretically that, contrary to preceding claims in the literature, ambiguity attitudes can play a role here. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 77 publications
1
4
0
3
Order By: Relevance
“…Epstein and Halevy (2019) found ambiguity aversion with CERIS first and no evidence for hedging. Baillon and Placido (2019) and Li et al (2020) Task-CERIS-Ambiguity also found some degree of ambiguity aversion with PERIS coming before the decision tasks. Both papers' average ambiguity premiums are slightly lower than that of Epstein and Halevy (2019), possibly due to the use of PERIS instead of CERIS.…”
Section: Empirical Evidence From the Literaturementioning
confidence: 93%
“…Epstein and Halevy (2019) found ambiguity aversion with CERIS first and no evidence for hedging. Baillon and Placido (2019) and Li et al (2020) Task-CERIS-Ambiguity also found some degree of ambiguity aversion with PERIS coming before the decision tasks. Both papers' average ambiguity premiums are slightly lower than that of Epstein and Halevy (2019), possibly due to the use of PERIS instead of CERIS.…”
Section: Empirical Evidence From the Literaturementioning
confidence: 93%
“…Without prior knowledge, all percentage chances between 30% and 80% are equally likely and when integrated over, one should expect the average success rate to be 55% (five points higher than the traditional treatment). Ambiguity aversion’s potential negative consequences are not only apparent with health decisions (Han et al, 2009 ) but extend across decision types, including social (Li et al, 2020 ) and career decisions (Xu, 2020 ). Given these potential negative consequences of ambiguity aversion, the goal of this study is to examine how the affective states arousal and stress affect ambiguity attitudes.…”
mentioning
confidence: 99%
“…Namun juga umumnya koperasi tidak memiliki alat evaluasi yang berbasis data sehingga strateginya kurang tepat sasaran. Penelitian menunjukkan bahwa dibawah strategi yang tidak tepat atau tidak pasti akan meningkatkan tingkat kerumitan sehingga berpengaruh terhadap pengambilan keputusan, karenanya hindari berspekolasi tanpa data (Li, Turmunkh, & Wakker, 2020).…”
Section: Kenggotaan Koperasiunclassified